Writing Centre Approach: Critical Issues and Practical Concerns. - Tan, Bee Hoon (Universiti Putra Malaysia Press, 2007)
As part of a research study on innovating the writing centre approach in Malaysian tertiary education, this paper critiques some common practices in writing centres, and raises issues pertinent to the writing centre approach. Critical issues discussed are the notion of help in writing centre tutoring, generalist versus specialist tutoring, peer review versus peer tutoring, tutoring ESL students, and grammar instruction. Examples are drawn from context where the writing centre was originally innovated to explore a workable model for its application in Malaysian tertiary institutions.